Kepemimpinan Transformasional, Kemitraan Industri, Kompetensi Guru, dan Inovasi yang Mempengaruhi Efektivitas Guru - Ramadhani Ramadhani; Aslamiah Aslamiah; Sutarto Hadi (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2025)
Abstract: This study aims to analyze the influence of transformational leadership of school principals, industry partnerships, teacher competence, and learning innovation on teacher work effectiveness in public vocational high schools (SMK) in Banjarbaru City. The urgency of this research is based on the increasing demands of globalization and technological development, which require teachers to be adaptive, competent, collaborative, and capable of implementing innovative learning practices. The study employed a quantitative approach with a correlational design. A total of 123 teachers were selected as respondents through proportional random sampling. Data were collected using a Likert-scale questionnaire that had been previously tested for validity and reliability. The analysis techniques included multiple regression, correlation, and path analysis, processed using SPSS version 27. The findings indicate that transformational leadership, industry partnerships, teacher competence, and learning innovation are categorized as good and significantly influence teacher work effectiveness. In addition to their direct effects, the three independent variables also exhibit indirect effects through learning innovation as a mediating variable. Learning innovation plays a crucial role in strengthening the relationship between leadership, partnerships with industry, and teacher competence toward improving teacher effectiveness. These results emphasize that teacher effectiveness is not solely determined by individual capability but also by supportive leadership practices and strategic collaboration with industry that enable teachers to implement technology-based innovative learning. The study recommends enhancing transformational leadership, strengthening teacher professional competence, and optimizing sustainable industry partnerships as strategic efforts to improve the overall quality of vocational education. Keywords: Transformational Leadership; Industry Partnership; Teacher Competence; Learning Innovation; Teacher Effectiveness. Abstrak: Penelitian ini bertujuan untuk menganalisis pengaruh kepemimpinan transformasional kepala sekolah, kemitraan dengan dunia industri, kompetensi guru, serta inovasi pembelajaran terhadap efektivitas kerja guru di Sekolah Menengah Kejuruan (SMK) Negeri Kota Banjarbaru. Permasalahan efektivitas kerja guru menjadi semakin penting seiring tuntutan era globalisasi dan perkembangan teknologi pembelajaran yang mengharuskan guru memiliki kemampuan adaptif, kolaboratif, dan inovatif. Penelitian ini menggunakan pendekatan kuantitatif dengan desain korelasional yang melibatkan 123 guru sebagai sampel yang dipilih melalui teknik proportional random sampling. Pengumpulan data dilakukan menggunakan kuesioner skala Likert yang telah melalui uji validitas dan reliabilitas. Teknik analisis meliputi regresi berganda, korelasi, dan analisis jalur (path analysis) yang diolah menggunakan SPSS versi 27. Hasil penelitian menunjukkan bahwa kepemimpinan transformasional, kemitraan industri, kompetensi guru, dan inovasi pembelajaran berada pada kategori baik serta berpengaruh positif dan signifikan terhadap efektivitas kerja guru. Selain pengaruh langsung, ketiga variabel utama juga terbukti memiliki pengaruh tidak langsung melalui inovasi pembelajaran sebagai variabel mediasi. Inovasi pembelajaran menjadi faktor penguat yang menjembatani hubungan antara kepemimpinan, kemitraan, dan kompetensi guru terhadap peningkatan efektivitas kerja. Temuan ini menegaskan bahwa efektivitas kerja guru tidak hanya ditentukan oleh kemampuan personal, tetapi juga oleh dukungan kepemimpinan yang visioner dan kolaborasi strategis dengan dunia industri. Penelitian ini merekomendasikan penguatan kepemimpinan transformasional, peningkatan kompetensi profesional guru secara berkelanjutan, serta optimalisasi kemitraan industri sebagai strategi penting untuk meningkatkan mutu pendidikan vokasi di SMK. Kata kunci: Kepemimpinan Transformasional; Kemitraan Industri; Kompetensi Guru; Inovasi Pembelajaran; Efektivitas Guru.